Oleanolic acid induces autophagic death in human gastric cancer cells in vitro and in vivo - Nie, Hao; Wang, Yu; Qin, Yong; Gong, Xing-Guo (Cell biology international, 2016)
Oleanolic acid (OA), a plant‐derived pentacyclic terpenoid, is known to have hepatoprotective effects. In this study, we found that OA induced autophagic cell death in multiple human gastric cancer cell lines. Moreover, OA‐induced autophagy was shown for the first time in human gastric cancer cells, evidenced by the formation of GFP‐RFP‐LC3 puncta and autophagosomes. OA suppressed phospho‐mTOR through inhibition of the PI3 K/AKT and ERK/p38 MAPK signalling pathways and through activation of the AMPK signalling pathway. Furthermore, we found that OA‐induced cytotoxicity and autophagy could be blocked by the autophagy inhibitor 3‐methyladenine or via siRNA targeting Beclin‐1. Our in vivo research showed that OA delayed the formation of MGC‐803 tumours in an autophagy‐dependent manner. These results reveal a novel mechanism for OA in gastric cancer cells and suggest that OA could be a novel agent in the treatment of gastric cancer.